BVGer D-4109/2019 vom 6. August 2019 - Bundesverwaltungsgericht (2019)
Asyl und Wegweisung (Mehrfachgesuch/Wiedererwägung) | Asyl und Wegweisung (Mehrfachgesuch/Wiedererwägung); Verfügung des SEM vom 6. August 2019